2018
DOI: 10.1371/journal.pone.0194439
|View full text |Cite
|
Sign up to set email alerts
|

Association of adverse childhood experiences and health risk behaviors among young adults visiting a regional primary healthcare center, Federation of Bosnia and Herzegovina

Abstract: BackgroundMany studies have linked adverse childhood experiences (ACEs) to long-term health outcomes, as well as health risk behaviors. In the post-war period in Bosnia and Herzegovina, many young people grew up in an environment of deteriorated living standards due to high unemployment and economic insecurity. The objectives of the study were to: 1) describe the health risk behaviors of young adults accessing primary healthcare; and 2) examine associations of these risk factors with adverse childhood experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…When all individual types of abuse were considered together in the current study, most relationships with adult violence outcomes were attenuated but remained significant, suggesting child abuse in general, regardless of type, increases the risk of PA, IPV, and SV in adulthood. Further, consistent with findings elsewhere [ 19 , 22 , 23 , 26 28 ], the current study demonstrated a cumulative impact of child abuse on risk of violence revictimisation. Compared to individuals who experienced no abuse in childhood, those who experienced one form of abuse were over twice as likely to report PA in the past year and three times as likely to have experienced IPV and/or SV since age 16 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When all individual types of abuse were considered together in the current study, most relationships with adult violence outcomes were attenuated but remained significant, suggesting child abuse in general, regardless of type, increases the risk of PA, IPV, and SV in adulthood. Further, consistent with findings elsewhere [ 19 , 22 , 23 , 26 28 ], the current study demonstrated a cumulative impact of child abuse on risk of violence revictimisation. Compared to individuals who experienced no abuse in childhood, those who experienced one form of abuse were over twice as likely to report PA in the past year and three times as likely to have experienced IPV and/or SV since age 16 years.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to those who had no history of ACEs, individuals with experience of one ACE were over one and a half times more likely to have been a victim of violence in the past year, increasing to over four times more likely for those with 2-3 ACEs, and over seven times more likely for those with four or more ACEs [19]. This doseresponse relationship between childhood adversity and experience of violence in adulthood has also been replicated in several studies across different countries [23][24][25][26]. To date however, there are a limited number of studies which examine the relationship between childhood abuse and different forms of adult interpersonal violence.…”
Section: Introductionmentioning
confidence: 73%
“…Among the ACE subtypes, emotional abuse (56.94 %) and emotional neglect (51.76 %) were the most commonly reported, followed by physical abuse (38.15 %) and physical neglect (38.12 %), suggesting a high prevalence of maltreatment and staggering incidence of emotional maltreatment. In a cross-sectional survey of 520 respondents from regional primary healthcare centers in Bosnia and Herzegovina, it was found that emotional neglect was the most common type of ACE (25.6 %) and was significantly more prevalent among women [ 23 ]. Another study showed that at least 30 % of participants reported emotional neglect and physical neglect, while 40 % reported emotional abuse [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…O ACE Study, realizado em San Diego e conduzido pelo Departamento de Medicina Preventiva da Kaiser Permanente ® em parceria com o Centro de Controle e Prevenção de Doenças dos Estados Unidos (CDC), é considerado um marco na investigação da exposição ao abuso e negligência durante a infância como fator de risco associado a desfechos negativos de saúde e bem-estar ao longo da vida 3,4 . A partir de sua publicação, diversos estudos epidemiológicos foram conduzidos, dando ênfase a uma crescente preocupação mundial sobre as consequências dos maus-tratos infantis, não somente imediatas, mas também a longo prazo [5][6][7] .…”
Section: Introductionunclassified